Teaching Aspects of Antibiotics and Antimicrobials to the Food Science Student through a Combination Wet Lab and In Silico Activity - Tahl Zimmerman (American Society for Microbiology, 2021)
ABSTRACT To prevent the growth of food pathogens and food spoilage organisms, antimicrobials are used to disinfect surfaces or are added to food. In light of the important role that antibiotics and antimicrobials play in food safety, food science students need a deep understanding of how these chemicals function. We describe here a combined wet lab and in silico laboratory experience designed to help students visualize two biochemical concepts explaining antibiotic activity: (i) bacteriolytic versus bacteriostatic activity and (ii) competitive versus noncompetitive inhibition. This laboratory experience was implemented for students enrolled in the Introduction to Food Science course in Family and Consumer Sciences at North Carolina A&T State University.